2020
DOI: 10.1093/condor/duaa041
|View full text |Cite
|
Sign up to set email alerts
|

Piping Plover population increase after Hurricane Sandy mediated by immigration and reproductive output

Abstract: Evaluating population-level responses to conservation action following large-scale disturbance can improve the efficacy of future habitat conservation measures. In October 2012, Hurricane Sandy storm surges cleared vegetation and opened inlets through the barrier islands, Fire Island and Westhampton Island, New York, creating Piping Plover (Charadrius melodus) habitat. Storm effects prompted an island-wide stabilization project, which had the potential to negatively affect novel Piping Plover habitat. Certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Therefore, it also is possible that the negative correlation between visitor counts and breeding abundance we observed is an indirect effect of growing visitor population on slowed immigration of new breeders. In a growing population in New York, the number of immigrants had, among demographic variables, the most important effect on population growth rate (Robinson et al, 2020). Moreover, at least 8 cases of piping plover population irruptions after storms created new habitat suggest that this species often is at or near carrying capacity (Robinson et al, 2019).…”
Section: Tablementioning
confidence: 99%
“…Therefore, it also is possible that the negative correlation between visitor counts and breeding abundance we observed is an indirect effect of growing visitor population on slowed immigration of new breeders. In a growing population in New York, the number of immigrants had, among demographic variables, the most important effect on population growth rate (Robinson et al, 2020). Moreover, at least 8 cases of piping plover population irruptions after storms created new habitat suggest that this species often is at or near carrying capacity (Robinson et al, 2019).…”
Section: Tablementioning
confidence: 99%
“…Of the known age piping plovers that return to nest on New Jersey beaches each year, as many as 45% are second-year birds (Stantial, personal observation). Robinson et al (2020) found that the population of piping plovers nesting in Fire Island on Long Island, NY, was primarily composed of returning adults and immigrants and that a low proportion of the population was made up of natal recruits (5-19%). Furthermore, Roche et al (2010) found that of the 31 Great Lakes piping plover adults that disappeared from 1993 to 2007, only 3 of them were second-year adults.…”
Section: Discussionmentioning
confidence: 99%
“…We searched for piping plover nests in all areas of suitable dry sand habitat within the study area, surveying each area every 1–3 days using a combination of walking surveys and intensive nest searching in areas where adult piping plovers exhibited nest defense behaviors (Walker et al 2019, Robinson et al 2020 a ). We estimated nest initiation dates by counting back 1.5 days per egg present for partial clutches (Wilcox 1959, Haig and Oring 1988) or by floating eggs for full clutches (Westerskov 1950), then used these initiation dates to estimate likely hatch dates, assuming 28 days of incubation.…”
Section: Methodsmentioning
confidence: 99%
“…Piping plover abundance within the study area has steadily increased since 2012 in response to an increase in suitable habitat following Hurricane Sandy along with habitat creation and protection efforts, with estimated densities of 0.09–0.12 pairs/ha across Fire Island and adjacent Westhampton Island (Walker et al 2019, Weithman et al 2019, Robinson et al 2020 a ). Managers enacted seasonal beach driving closures and erected symbolic string fencing to exclude people from nesting areas during the shorebird breeding season (April–August).…”
Section: Study Areamentioning
confidence: 99%